2008
DOI: 10.1111/j.1524-475x.2008.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotide stimulates angiogenesis and wound healing in the genetically diabetic mouse

Abstract: Healing of diabetic wounds still remains a critical medical problem. Polydeoxyribonucleotide (PDRN), a compound having a mixture of deoxyribonucleotide polymers, stimulates the A2 purinergic receptor with no toxic or adverse effect. We studied the effects of PDRN in diabetes-related healing defect using an incisional skin-wound model produced on the back of female diabetic mice (db1/ db1) and their normal littermates (db1/1m). Animals were treated daily for 12 days with PDRN (8 mg/kg/ip) or its vehicle (100 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
152
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 34 publications
4
152
0
1
Order By: Relevance
“…A 2A receptors are expressed on different cell types, especially under ischemic conditions. [23][24][25][26][27] These observations, together with our previous findings on the ability of PDRN to induce VEGF expression during altered healing conditions such as diabetes 11 and burn injury, 12 acting through the A 2A receptor, led us to hypothesize that PDRN could be also efficacious in stimulating VEGF and revascularization in the ischemic limb. Indeed, in this study we demonstrated the beneficial role of Femoral artery ligation and excision provoked an immediate impairment in perfusion, as revealed by laser Doppler flowmetry that persisted after 21 days after the surgical procedures.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A 2A receptors are expressed on different cell types, especially under ischemic conditions. [23][24][25][26][27] These observations, together with our previous findings on the ability of PDRN to induce VEGF expression during altered healing conditions such as diabetes 11 and burn injury, 12 acting through the A 2A receptor, led us to hypothesize that PDRN could be also efficacious in stimulating VEGF and revascularization in the ischemic limb. Indeed, in this study we demonstrated the beneficial role of Femoral artery ligation and excision provoked an immediate impairment in perfusion, as revealed by laser Doppler flowmetry that persisted after 21 days after the surgical procedures.…”
Section: Discussionmentioning
confidence: 81%
“…10 Polydeoxyribonucleotide (PDRN) is a compound that, acting through adenosine receptors, is able to stimulate VEGF production during pathologic conditions of low tissue perfusion such as diabetes mellitus and thermal injury. 11,12 PDRN is the active fraction of a preparation used in therapy as an agent to stimulate tissue repair and is extracted from the sperm of trout bred for human consumption. The drug is obtained by an extraction process with purifying and high temperature sterilizing procedures to obtain an Ͼ95% pure active principle without pharmacologically active proteins and peptides (Registration Dossier, Italian Ministry of Health).…”
mentioning
confidence: 99%
“…3 Angiogenesis plays a fundamental role in the wound healing process, so wherever the vascular conditions are lacking at the surgical site, consistent neoangiogenetic stimuli could enhance the healing of the wound. [13][14][15] The results described here suggest that PEG is able to interact with the host tissue without any inflammatory reaction, regardless of the previous preconditioning of the material with other substances. In addition, we have demonstrated an increase in blood flow and angiogenesis in the area where PEG was inserted in combination with EMD, which was able to further improve PEG integration in the host tissues as well as the angiogenic response for up to 8 weeks.…”
Section: Discussionmentioning
confidence: 63%
“…PDRN is helpful for normal matrix formation by shortening the healing period through its prompt tissue regeneration and wound healing and by promoting the creation of collageneous/ noncollageneous protein. Also, it is characterized by being effective in tissue regeneration by promoting cell regeneration in cellular stage [9][10][11][12][13][14] . In 2008, an autogenous bone graft material was developed from extracted teeth, and subjected to many basic and clinical studies.…”
Section: Discussionmentioning
confidence: 99%